Ask the Experts: Chromatographic baselines. (May 2014) - Unknown
Bioanalysis invited a selection of leading researchers to express their views on chromatographic baseline assignment in the bioanalytical laboratory. The topics discussed include the challenges presented with ensuring automated baseline assignment is correct, when reintegration is necessary, regulation and consistency in terminology. Their enlightening responses provide a valuable insight into developing an industry consensus towards reintegration. An accompanying commentary article in this issue, authored by Howard Hill and colleagues (Huntingdon Life Sciences), provides background to this much debated topic.